Functions and clinical significance of circular RNAs in acute myeloid leukemia - Zhou, Min; Gao, Xianling; Zheng, Xin; Luo, Jing (Frontiers in Pharmacology, 2022)
Circular RNAs (circRNAs) are a class of covalently closed single-stranded RNA molecules. Four types of circRNAs have been reported in animal cells, and they have typical characteristics in their biogenesis, nuclear export and degradation. Advances in our understanding of the molecular functions of circRNAs in sponging microRNAs, modulating transcription, regulating RNA-binding proteins, as well as encoding proteins have been made very recently. Dysregulated circRNAs are associated with human diseases such as acute myeloid leukemia. In this review, we focus on the recently described mechanisms, role and clinical significance of circRNAs in acute myeloid leukemia. Although great progress of circRNAs in AML has been achieved, substantial efforts are still required to explore whether circRNAs exert their biological function by other mechanisms such as regulation of gene transcription or serving as translation template in AML. It is also urgent that researchers study the machineries regulating circRNAs fate, the downstream effectors of circRNAs modulatory networks, and the clinical application of circRNAs in AML.